PERSPEKTIF KEADILAN IKLIM DALAM INSTRUMEN HUKUM LINGKUNGAN INTERNASIONAL TENTANG PERUBAHAN IKLIM - Bram, Deni (Faculty of Law, Universitas Jenderal Soedirman, 2011)
The issue of climate change has become a central point of attention the world community on this century. In scientists view says that if we fail to make significant reductions in greenhouse gas emissions for ten to twenty years ahead, we face the possibility of harmful environmental disaster at the end of this century. Legal instruments at international level which is present as a step to mitigate climate change were felt only in the interests of developing countries alone that puts the asymmetric advantage. The concept of climate justice is felt not touched so that the regime to combat climate change often fail in the fulfillment of justice for present and future.Keywords: climate change, intergenerational equity, intra generational equity